Phenomenology of religion as vіa medіa: on potentialities of the phenomenological approach to integration of philosophy of religion and theology - Cherenkov, Mykhailo (Skhid, 2015)
The paper deals with relations between philosophy of religion, theology and phenomenology within the changeable structure of scientific knowledge. It is religion itself as religious life in its immediacy and almost physical reality (without any unnecessary ’super’ structures) rather than philosophical or theological knowledge as knowledge of religion, which becomes the subject matter of phenomenology. With this immediacy (the non-metaphysic and non-theoretical nature), potentialities of the scientific phenomenological approach are preserved because life does not remain indifferent to questions of the subject who cognizes and is open to reflexion, questions, doubts and research. Phenomenology is regarded as via media, tsar’s way, which combines potentialities of philosophy of religion and Christian theology. Philosophy of religion remains external and neutral to the processes, Christian theology being internal and involved in the latter. Phenomenology is used to make Christian theology at least partially accessible for philosophy of religion. In this way the role of phenomenology is intermediary and integrative. In propinquity to philosophy of religion and theology, phenomenology which serves both and enriches itself through both can be reasonably called ’vіa medіa’.